Assessing the Effectiveness of Tax Reduction Policies in Rejuvenating Indonesian Automotive Industry Productivity Post-COVID-19 - Amin, Abdusy Syakur (Khazanah Sosial, 2023)
This study examines the governmental strategy implemented by the Indonesian Government to mitigate the repercussions of the COVID-19 pandemic on the Indonesian automotive industry. The government introduced a policy involving tax incentives, particularly targeting domestic manufacturers producing automobiles. The primary objective of this policy was to sustain industry operations, albeit within limited capacities, amidst the challenging circumstances posed by the pandemic. The provision of these incentives was formalized through the issuance of PMK No 20/PMK.010/21, addressing Sales Tax on Luxury Goods for the Delivery of Taxable Goods Classified as Luxury, specifically pertaining to certain motorized vehicles, sponsored by the government during the fiscal year 2021. This study analyzes a comparative analysis utilizing the T-test methodology on car sales data prior to and subsequent to the implementation of the tax incentive policy. The data processing was executed through the Statistical Package for the Social Sciences (SPSS). The results of the incentive application analysis reveal a notable disparity in sales figures before and after the policy's enforcement. Thus, it is concluded that the tax incentives implemented by the government are effective in increasing car sales during the COVID-19 pandemic. Consequently, the government's policy measures not only yield advantages for entrepreneurs engaged in manufacturing but also extend benefits to the broader public as consumers. This underscores the practical impact of the policy, aligning with the realities observed in society thus far.